Perspectives of adolescents from low-income households in Berlin—nutrition described by food affordability, household routines and autonomy: results from an exploratory qualitatively-driven mixed-methods study of cases - Sarah B. Blakeslee; Anne Schirmaier; Lara Steyer; Steven Ngandeu Schepanski; Georg Seifert; Wiebke Stritter; Gonza B. Ngoumou (Frontiers in Public Health, 2026)
Introduction Food insecurity threatens the nutritional intake of young people, including their health and well-being. It is known that the link between nutrition and low income exacerbates socioeconomic disparities. In Germany, low-income families are entitled to subsidies, but evidence suggests that financial assistance is insufficient for an adequate diet. Young people from low-income families are affected by this, but little is known about their experiences. Materials and methods A two stage, qualitatively-driven, exploratory, mixed-method study with consecutive design was undertaken with young people (14–17 years) from low-income households in Berlin. Photo-documentation, interviews and participant observation were conducted, and quantitative data was gathered on nutrition, health, wellbeing and financial situation of young people and their families. Data types were analyzed thematically and descriptively, then reported as cases. Results In total, six young participant cases (5 female, 1 male), with a median family weekly food expenditure of 150 € completed the first stage of the study and most rated health and nutrition as important. Recruitment was very challenging, and only one of the participant completed all parts of the second stage. Therefore, additionally three youth experts were interviewed. In the narratives of the young people two important and distinctive settings for consuming food emerged: (1) eating within the family setting versus (2) external food consumption. Both in interviews and family’s meal observations, the daily organization, preferences and practices were guided by parents and mostly accepted by the young people within the home. Observed shopping trips and interview narratives about finances underscored awareness of the young people about family finances. School was not considered a conducive environment for finding nutritious and affordable food options. Friends, school peers and social media trends influenced consumption habits. Young people developed strategies to access desired foods that became part of their developing autonomy. Conclusion The study provides valuable and underrepresented insights into the food environments of young people from low-income households in Berlin with an integrated methodological approach, showing how their everyday experiences with food, health and nutrition centered on the home and independence articulated among peers. Lack of access to healthy, affordable food at school underscores income discrepancies among pupils. Clinical trial registration https://drks.de/search/de/trial/DRKS00031853 Identifier DRKS00031853.